Dysarthria and other-initiated repair in everyday conversation. - Bloch, Steven; Barnes, Scott (Clinical Linguistics & Phonetics, 2020)
Dysarthria is commonly understood as a motor speech disorder characterized by symptoms that are framed as physiologically or acoustically measurable. The effects of dysarthria on social interaction through conversation have been reported but, in comparison with physical measures, remain relatively unexplored. Other-initiated repair sequences are particularly common in dysarthria-in-interaction, drawing attention to the actions of both participants in managing (un)intelligibility, rather than the behavior(s) of the person with dysarthric speech in isolation. These sequences merit detailed and ongoing investigation as they enable us to understand how dysarthria impacts on conversation and, critically, how participants attempt to manage difficulties when they arise. This study explores the organization of other-initiated repair sequences in a dyad where one participant has severe dysarthria arising from amyotrophic lateral sclerosis (ALS) also known as MND. Two hours of recordings were collected on four dates over a 12-month period with the data presented here from recording two. The evidence shows that the participants were able to resolve their troubles, but it required extensive work to both identify the trouble sources and to unravel the problems to reach a satisfactory understanding. The interactions presented in this paper reveal an important limitation of other initiation of repair. Physical restrictions were seen to play an important part in the dysarthric speaker's ability to position his talk in sequential context and successfully accomplish self-repair; particularly, third-turn repair. The present study has offered a depiction of layered conversational problems that other-initiation of repair may not completely resolve or, in some cases, multiply.